Motion-Controlled Virtual Reality Robotic Arm With Kinect - Demir, Tugberk; Mutlu, Ugur; Yildirim, Tulay (IEEE, 2018)
Kinect is a technology developed by Microsoft that perceives human movements and plays with these movements. On the other hand, virtual reality creates the feeling that we are in an environment that we are not actually in. Purpose of this work is to develop a robotic arm that repeats nonsensitive movement of the person through Kinect and through the camera, it is aimed to see the environment in which the robotic arm is placed virtually. With the combination of Kinect technology and VR technology, full control and realism are provided to the user from a distance. This feature distinguishes the proposed approach from other studies. When human health and work accidents are considered, this system is intended to increase safety and protect human health in dangerous environment.
Keywords: Kinect; Virtual Reality; Robotic Arm; Computer Science; Engineering